Common variable immunodeficiency-associated heterozygous transcription factor 3 (TCF3) gene mutations in two pediatric cases - Özdemir, Öner; Dikici, Ümmügülsüm; Yarar, Murat Hakkı (Alergologia Polska - Polish Journal of Allergology, 2025)
Common variable immunodeficiency (CVID) is one of the predominant antibody deficiencies and the most common symptomatic inborn error of immunity (IEI). However, in most cases, the genetic background of the disease cannot be identified. Various immunological and genetic defects play a role in the pathogenesis of CVID. B cells are the cells responsible for the humoral immune response, in other words, for antibody formation. Transcription factors play a role in B cell development and differentiation. One of the genes encoding these proteins is transcription factor 3 (TCF3). In this report, we present the laboratory results and clinical course of two pediatric cases with de novo heterozygous TCF3 mutations. Genetic examination should be performed in patients with the diagnosis of CVID who are followed up and have additional findings. Identified genetic mutations have an important place in the clinical follow-up and the phenotype of the disease is determined by case reports. Our case report contributes to the laboratory and clinical presentation of IEI due to TCF3 mutation.